Oxford handbook of clinical skills for children's and young people's nursing - Dawson, Paula (Oxford handbooks in nursing., 2012)
Children's nurses are faced with unique challenges when undertaking clinical skills, adapting their knowledge and practice for the physical and developmental age of their patients. The Oxford Handbook of Clinical Skills for Children's and Young People's Nursing is a practical guide to both the most basic and the increasingly complex elements of caring for the health needs of children and young people. Focusing on the key principles underpinning all elements of care, it provides asolid, evidence-based framework which practitioners can use to develop their clinical knowledge, skills, and attitudes. It systematically covers the body systems and the clinical skills relating to them, and includes additional tips and suggested courses of action when encountering difficulties with aprocedure, with practical advice from current practitioners. Written by experienced children's nurses working either within clinical paediatric settings or as educators in the field, this handbook is an essential, quick, and reliable practice reference tool for any clinical setting.